Citation Analysis of Mathematics and Statistics Dissertations and Theses from the University at Albany. Issue 2 (2nd April 2020) - Flynn, Kathleen Hutchinson
ABSTRACT: This study analyzed dissertations and theses completed from 2009–2019 in the Mathematics and Statistics department at the University at Albany to investigate resource type, citation age, publishers, and journal title dispersion. Students cited journal articles 57.0% of the time, while books and book chapters combined accounted for 30.5% of the citations. Publisher usage fit the Pareto Distribution; however, there was a high journal title dispersion. Preprints represented 4.6% of the citations, an increase from previous studies. The amount of graduate student citation quality issues and preprint citations shows a need for instruction and discussions in these areas.